Pengaruh Good Corporate Governance, Modal Intelektual, Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Makanan - Arief Abdul Aziz; Yuli Chomsatu Samrotun; Riana Rachmawati Dewi (Ekonomis: Journal of Economics and Business, 2021)
The purpose of the study is to test the impact of good corporate governance, intellectual capital, and corporate size on food and beverage performance. This study sample is a food and beverage company registered in the Indonesian stock exchange. The analysis used in this study is linked to linear regression analysis. Studies show that good corporate governance consists of a few indicators, these indictments show that the size of the board of commissioners affects financial performance (roa), independent commissioners have no effect on financial performance (roa), and independent auditing committees affect financial performance (roa) and institutional ownership. No influence on financial performance (roa), the manager's ownership has no effect on financial performance (roa), and the committee's size also affects financial performance (roa). Apart from good company governance indicators, intellectual capital has no effect on financial performance (roa), and the company's size also affects financial performance.